CLINICAL AND LABOATORY CHARACTERISTICS OF PSYCHOEMOTIONAL DISORDERS IN CHILDREN WITH DIABETES MELLITUS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This review article attempts to analyze and systematize the existing data in contemporary scientific literature on the etiology, pathogenesis, and clinical manifestations of cognitive and emotional deficits in children and adolescents with type 1 diabetes mellitus (T1DM). The publication is aimed at neurologists and pediatricians. Currently, type 1 diabetes in children and adolescents remains one of the most significant medical and social problems of modern society, requiring comprehensive and thorough study, followed by maximum optimization of therapeutic and rehabilitation measures. Chronic hyperglycemia underlies the development of cognitive and psycho-emotional disturbances in T1DM. The prevalence of neurological disorders in T1DM, according to some authors, varies widely—from 10% to 74%—and often depends on factors such as age at disease onset, disease duration, baseline glycemic levels, diagnostic criteria used, and others. Nervous system pathology in diabetes is observed in approximately 50% of pediatric patients with disease duration of 3 years or more, while up to 25-30% of children with recently diagnosed diabetes already exhibit established neurological changes.